2003
DOI: 10.1093/humrep/deg471
|View full text |Cite
|
Sign up to set email alerts
|

Can history, ultrasound, or ELISA chlamydial antibodies, alone or in combination, predict tubal factor infertility in subfertile women?

Abstract: Medical history, TVU appearances, and ELISA IgG CAT alone, or in combination, failed to predict accurately TFI in subfertile women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 24 publications
2
19
0
2
Order By: Relevance
“…28 Clinical history is not reliable in making a diagnosis of Chlamydial infection. 29,30 and WHO estimate that 70-75% of women with Chlamydia trachomatis infection are asymptomatic. 6 Since, this organism is highly prevalent and asymptomatic, a screening programme has been established in some industrialized countries to reduce the rate of PID and its reproductive sequelae.…”
mentioning
confidence: 99%
“…28 Clinical history is not reliable in making a diagnosis of Chlamydial infection. 29,30 and WHO estimate that 70-75% of women with Chlamydia trachomatis infection are asymptomatic. 6 Since, this organism is highly prevalent and asymptomatic, a screening programme has been established in some industrialized countries to reduce the rate of PID and its reproductive sequelae.…”
mentioning
confidence: 99%
“…Les publications colligeant les pathologies pelviennes retrouvées en coelioscopie chez des femmes séronégatives objective la faible sensibilité (67 %) de cet examen, même s'il est couplé à une anamnèse et à une échographie pelvienne [11]. Dans la méta-analyse de Mol et al [12], la sérologie Chlamydiae montre des résultats comparables à ceux de l'HSG dans le diagnostic d'obstruction tubaire ou d'hydrosalpinx.…”
Section: Sérologie Chlamydiaeunclassified
“…[31][32][33][34][35][36][37][38][39][40][41][42][43][44] The exact definition of tubal pathology was not described in nine studies. 14,15,18,22,24,[27][28][29]31 In the other 23 articles, the definition was mentioned according to predefined criteria.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…In 18 studies, both HSG and DLS were used as reference tests. [13][14][15]17,18,20,[23][24][25]27,32,33,[35][36][37][38][39]43 In five studies, a HSG was used to identify tubal pathology. 16,22,30,40,44 Eight studies reported laparoscopy as the reference standard.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation